Assessment of Drug-Related Problems and Health-Related Quality of Life in Medication Management of Hypertensive and Diabetic Patients at Two Referral Health Facilities: A Prospective Study - Ganiyu, Kehinde A.; Erah, Patrick O. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Evaluation of drug-related problems (DRPs) and patients’ health-related quality of life (HRQoL) are important in determining outcomes of medication management of hypertension and/or diabetes mellitus (DM). The study assessed the impact of pharmacist-led health educational intervention in reducing incidence of DRPs and improvement of HRQoL in the management of hypertensive and/or diabetic patients attending clinics at the two main tertiary health facilities in Bayelsa State, Nigeria. In a prospective study, 430 hypertensive and/or diabetic patients who attended clinics in 2011 – 2015 at the study centers were purposively recruited, and their medication use and HRQoL data gathered using pretested data collection form and Short form-12v2TM Health Survey questionnaire, respectively. Prescribed medications and patients’ HRQoL were assessed for DRPs and physical/mental health status, accordingly. Patient- and healthcare professional- (comprising physicians, pharmacists, and nurses) focused health-educational intervention was conducted and followed up for a 10-month period. The 307 patients not lost to follow-up were re-evaluated for DRPs and HRQoL and compared with their pre-intervention data. P-value < 0.05 at 2-tailwas considered significant. General population norm (mid-point score) of 50 ± 10 and minimal important difference (MID) of 3.0 units were adopted for the determination of HRQoL status and improvement, respectively. Average DRP number per encounter decreased from 1.24 ± 1.02 to 0.48 ± 0.67 (p < 0.0001) following intervention, with percentage DRP decrease of 60.0%. Virtually all MIDs for all subscales of physical/mental health summary scores indicated no improvement in the patients’ HRQoL. Twenty one and 36.0% of the report sample were at risk of screening positive for depression before and after intervention, respectively. The intervention produced substantial decrease in the DRPs observed in the patients’ medication therapy, though, there was no improvement in their HRQoL.